2020
DOI: 10.1021/acs.est.9b07463
|View full text |Cite
|
Sign up to set email alerts
|

Linkage between Particulate Matter Properties and Lung Function in Schoolchildren: A Panel Study in Southern China

Abstract: While several scientific studies have linked PM2.5 to decreased lung function, there is still some degree of uncertainty regarding which particulate physicochemical properties are most harmful. We followed a panel of 57 healthy schoolchildren (857 person-days) to investigate the associations between a wide variety of PM2.5 and lung function in Heshan, China in 2016 for three periods. We monitored the daily concentrations of mass, chemical composition, size, number, surface area, and volume of particulate mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…For example, exposure to sulfate, ammonium, EC, and/or OC fractions of PM 2.5 was adversely associated with pediatric emergency department visits for asthma and wheezing [22], and upper respiratory infections [23] among children in the United States. A panel study in Southern China also reported an association between OC and lung function decline in healthy school children [24]. Our previous study in the same city (Isahaya only) for adults with asthma showed consistent ndings that severe respiratory decline was associated with increased sulfate and OC fractions of PM 2.5 [7].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…For example, exposure to sulfate, ammonium, EC, and/or OC fractions of PM 2.5 was adversely associated with pediatric emergency department visits for asthma and wheezing [22], and upper respiratory infections [23] among children in the United States. A panel study in Southern China also reported an association between OC and lung function decline in healthy school children [24]. Our previous study in the same city (Isahaya only) for adults with asthma showed consistent ndings that severe respiratory decline was associated with increased sulfate and OC fractions of PM 2.5 [7].…”
Section: Discussionsupporting
confidence: 52%
“…A major strength of this study was that we obtained a large number of daily PEF measurements over three years in the spring, while most previous panel studies investigating the associations with PM 2.5 exposures have been designed to collect lung function measurements over multiple days or a few months [24,[29][30][31][32]. The large number of PEF measurements in our study could increase the statistical power to detect a smaller effect size for the exposure-response associations among children with asthma, who are one of the most vulnerable populations to air pollution exposure.…”
Section: Discussionmentioning
confidence: 99%
“…For example, exposure to sulfate, ammonium, EC, and/or OC fractions of PM 2.5 was adversely associated with pediatric emergency department visits for asthma and wheezing [ 22 ], and upper respiratory infections [ 23 ] among children in the United States. A panel study in Southern China also reported an association between OC and lung function decline in healthy school children [ 24 ]. Our previous study in the same city (Isahaya only) for adults with asthma showed consistent findings that severe respiratory decline was associated with increased sulfate and OC fractions of PM 2.5 [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…A major strength of this study was that we obtained a large number of daily PEF measurements over three years in the spring, while most previous panel studies investigating the associations with PM 2.5 exposures have been designed to collect lung function measurements over multiple days or a few months [ 24 , 29 32 ]. The large number of PEF measurements in our study could increase the statistical power to detect a smaller effect size for the exposure-response associations among children with asthma, who are one of the most vulnerable populations to air pollution exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Particulate matter with an aerodynamic diameter of 2.5 μm or less (PM 2.5 ) is one of the most harmful pollutants to lung health. Recently, several studies have shown that air pollution adversely affects lung function in children, adolescents, and adults ( 10 , 13 15 ). Furthermore, there is growing epidemiological evidence that long-term exposure to air pollution, especially PM 2.5 and nitrogen dioxide (NO 2 ), in healthy people or in people with certain chronic lung diseases, is associated with lower forced lung capacity (FVC) and forced expiratory volume in 1 s (FEV1) ( 11 , 12 , 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%